2017
DOI: 10.2807/1560-7917.es.2017.22.31.30583
|View full text |Cite|
|
Sign up to set email alerts
|

Evolving beta-lactamase epidemiology in Enterobacteriaceae from Italian nationwide surveillance, October 2013: KPC-carbapenemase spreading among outpatients

Abstract: Extended-spectrum beta-lactamases (ESBLs), AmpC-type beta-lactamases (ACBLs) and carbapenemases are among the most important resistance mechanisms in Enterobacteriaceae. This study investigated the presence of these resistance mechanisms in consecutive non-replicate isolates of Escherichia coli (n = 2,352), Klebsiella pneumoniae (n = 697), and Proteus mirabilis (n = 275) from an Italian nationwide cross-sectional survey carried out in October 2013. Overall, 15.3% of isolates were non-susceptible to extended-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 47 publications
1
31
2
Order By: Relevance
“…Prevalence was reported to be as low as 0.1% upon hospital admission in Germany [61] and 0.4% among hospitalised acute care patients in southern France in 2012 [62]. In Italy, 8% of clinical Enterobacteriaceae isolates from inpatients were carbapenem-resistant in 2013 [63]. In Switzerland, according to national laboratory-based surveillance data, absolute numbers of CPE have been increasing in recent years, with OXA-48 being the most commonly reported carbapenemase followed by K. pneumoniae carbapenemase [64].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence was reported to be as low as 0.1% upon hospital admission in Germany [61] and 0.4% among hospitalised acute care patients in southern France in 2012 [62]. In Italy, 8% of clinical Enterobacteriaceae isolates from inpatients were carbapenem-resistant in 2013 [63]. In Switzerland, according to national laboratory-based surveillance data, absolute numbers of CPE have been increasing in recent years, with OXA-48 being the most commonly reported carbapenemase followed by K. pneumoniae carbapenemase [64].…”
Section: Discussionmentioning
confidence: 99%
“…The situation in Denmark may not be representative for other settings. For example, a paper from Rosslini et al, in this issue [ref 12 ] shows that resistance in Italy is high. Their surveillance project (in October 2013) in several Italian hospitals, found that a quarter of all Klebsiella pneumoniae isolates from hospitalised patients were resistant to carbapenems.…”
Section: What Should the Conclusion From These Findings Be?mentioning
confidence: 99%
“…T he worldwide distribution of plasmid-mediated colistin resistance determinants (mcr-1, mcr-2, mcr-3, and mcr-4) coupled to the emerging observation that colistin resistance is more prevalent in carbapenem-resistant Enterobacteriaceae (CRE) (1,2) presents a daunting challenge in combatting antimicrobial resistance. Undoubtedly, next-generation sequencing approaches have expedited the discovery of mobile colistin resistance determinants (3).…”
mentioning
confidence: 99%